Pengaruh Sales Promotion, Product Quality, dan Hedonic Behavior pada Impulse Buying - Septiana, Irma; Widyastuti, Widyastuti (Jurnal Ilmu Manajemen, 2021)
A pandemic causes transactions in e-commerce to increase in health products. During the pandemic, impulsive purchases in e-commerce increased due to lockdown and fear of price increases. This research focuses on impulsive online purchases that are influenced by sales promotions, product quality, and hedonistic behavior. This type of research approach is quantitative with a causality research design. This analysis uses primary and secondary data sources. Data collection method using google form. Question measurement using a 5-point Likert scale. The population is infinite, and the number of samples collected is 197, which corresponds to the characteristics of the respondents is 123 respondents—the statistical analysis using multiple linear regression. The research results state that of the three independent variables, the hedonic behavioural variable significantly affects consumers' impulsive purchases of health products in e-commerce. Other variables, namely sales promotion and product quality, has no significant effect on impulsive purchases.